Schleiermacher And Palmer: The Father And Mother Of The Modern Protestant Mindset, by Justin A. Davis - Wojciechowski, Jennifer Hornyak (Word & world, 2021)
Word & World is a quarterly journal of theology whose readers are concerned with Christian ministry in and for the world.